Quality of Pain Management among Post-Operative Patients in Bir Hospital - Niraula, Hira Kumari; Shrestha Niraula, Goma Devi; D.C., Anita; Shrestha, Sarita; Joshi, Laxmi Devi; Tharu, Nanda Kumar; Bhattarai, Dr Nirajan; Bhatta, Dr Chet Raj; Maharjan, Mankeshari (Journal of Karnali Academy of Health Sciences, 2022)
Background: Most of the patients experienced pain after surgery. Inadequately managed pain affects the physiologicaland psychological state of the patient, interferes with daily activities, reduces the satisfaction of care provided, andinterferes with quality of life. The study aims to assess the quality of pain management among admitted postoperativepatients of Bir Hospital, Nepal.Methods: A descriptive cross-sectional study was conducted at the National Academy of Medical Science, Bir Hospitalusing the Revised American Pain Society Patient Outcome Questionnaire and patients’ charts. A total of 352 post-operative patients were interviewed. Descriptive statistics were used to analyze the severity of pain, and satisfaction levels.Spearman’s correlation coefficient, chi-square test, and ordinal logistic regression were used as an analytical approachusing SPSS Version 16.Results: About 95.2% of patients reported postoperative pain during the first 24 hours after surgery with a mean painintensity score of 4.9±2.3. Of these patients, 44.3% had moderate, and 27.8% had severe pain. The mean satisfaction withthe quality of postoperative pain management was 4.6 ± 2.3. Only 21.6% were very satisfied with pain management.There was a significant positive correlation between the pain intensity score with the interference of physical andemotional activities. Satisfaction with quality of pain management was significantly associated with the patient’s demandfor pain medications and intensity of pain. The satisfaction with the quality of pain management was 3.4 times, 7.1 times,and 8.7 times more likely in moderate, mild, and no pain intensity in comparison to severe pain intensity respectively.Conclusion: The majority of postoperative patients experienced moderate to severe pain and the majority of patientswere only moderately satisfied with the quality of pain management. Hence, additional efforts are required to reducepostoperative pain and improve the quality of pain management.